Unveiling the Disease Patterns and Infection Categories in MDRO-Infected Patients: Insights from a Comprehensive Study at Dr. Kariadi Hospital, Semarang - Ntambi, Saidi; Sutiningsih, Dwi; Laksono, Budi; Maiga, Ayub Hussein; Mujahidah, Mujahidah (Jurnal Epidemiologi Kesehatan Komunitas, 2024)
Background: Multi-drug resistant organisms (MDRO) pose a significant challenge to healthcare systems worldwide, leading to increased morbidity, mortality, and healthcare costs. Understanding the disease patterns and infection categories associated with MDRO infections is crucial for effective management and prevention strategies. This study aims to unveil the prevalent diseases and infection categories among MDRO-infected patients at Dr. Kariadi Hospital, Semarang in Indonesia.Methods: A comprehensive retrospective analysis was conducted on medical records of patients diagnosed with MDRO infections. Clinical characteristics were collected and analyzed. The diseases were classified into broader categories based on their organ system or common medical classification.Result: The study included 100 MDRO-infected patients and they presented with 81 various medical conditions/diseases. The most common diseases associated with MDRO infections were Covid-19, and Bronchopneumonia. Among the infection categories, gastrointestinal disorders, and Neoplastic Diseases were the predominant categories. The study revealed a high prevalence of MDRO infections in patients with these conditions while as the category of Autoimmune and Rheumatic Diseases accounted for the smallest proportion of cases with only one case.Conclusion : This comprehensive study provides valuable insights into the disease patterns and infection categories in MDRO-infected patients at Dr. Kariadi Hospital, Semarang. The findings highlight the need for targeted surveillance, infection control measures, and antimicrobial stewardship programs to effectively manage MDRO infections. Understanding the most prevalent diseases and infection categories associated with MDROs can aid in early detection, appropriate treatment, and the development of preventive strategies.